Pancreatitis severity in mice with impaired CFTR function but pancreatic sufficiency is mediated via ductal and inflammatory cells‐Not acinar cells. Issue 10 (8th March 2021) - Trapp, Simon; Aghdassi, Ali A.; Glaubitz, Juliane; Sendler, Matthias; Weiss, Frank Ulrich; Kühn, Jens Peter; Kromrey, Marie‐Luise; Mahajan, Ujjwal M.; Pallagi, Petra; Rakonczay, Zoltán; Venglovecz, Viktória; Lerch, Markus M.; et al.
Abstract: Mutations in the cystic fibrosis transmembrane conductance regulator gene ( CFTR ) are an established risk factor for cystic fibrosis (CF) and chronic pancreatitis. Whereas patients with CF usually develop complete exocrine pancreatic insufficiency, pancreatitis patients with CFTR mutations have mostly preserved exocrine pancreatic function. We therefore used a strain of transgenic mice with significant residual CFTR function (CFTR tm1HGU ) to induce pancreatitis experimentally by serial caerulein injections. Protease activation and necrosis were investigated in isolated acini, disease severity over 24h, pancreatic function by MRI, isolated duct stimulation and faecal chymotrypsin, and leucocyte function by ex vivo lipopolysaccharide (LPS) stimulation. Pancreatic and lung injury were more severe in CFTR tm1HGU but intrapancreatic trypsin and serum enzyme activities higher than in wild‐type controls only at 8h, a time interval previously attributed to leucocyte infiltration. CCK‐induced trypsin activation and necrosis in acini from CFTR tm1HGU did not differ from controls. Fluid and bicarbonate secretion were greatly impaired, whereas faecal chymotrypsin remained unchanged. LPS stimulation of splenocytes from CFTR tm1HGU resulted in increased INF‐γ and IL‐6, but decreased IL‐10 secretion. CFTR mutations that preserve residual pancreatic function significantly increase the severity of experimental pancreatitis—mostly via impairing duct cell function and a shift towards a pro‐inflammatory phenotype, not by rendering acinar cells more susceptible to pathological stimuli.